Hydrophobic functionalization reactions of structured cellulose nanomaterials: Mechanisms, kinetics and in silico multi-scale models. (1st May 2021) - Oberlintner, Ana; Likozar, Blaž; Novak, Uroš
Highlights: Overview of hydrophobic functionalization reactions of nanocellulose. Insight look and the description of the mechanism. Presented in-silico modelling approaches. Representation of the hydrophobic nanocellulose materials utilization. Abstract: Nanoscale-interfaced cellulose nanomaterials are extracted from polysaccharides, which are widely available in nature, biocompatible and biodegradable. Moreover, the latter have a potential to be recycled, upcycled, and formulate therefore a great theoretical predisposition to be used in a number of applications. Nanocrystals, nano-fibrils and nanofibers possess reactive functional groups that enable hydrophobic surface modifications. Analysed literature data, concerning mechanisms, pathways and kinetics, was screened, compared and assessed with regard to the demand of a catalyst, different measurement conditions and added molecule reactions. There is presently only a scarce technique description for carbonOH bond functionalization, considering the elementary chemical steps, sequences and intermediates of these (non)catalytic transformations. The overview of the prevailing basic research together with in silico modelling approach methodology gives us a deeper physical understanding of processes. Finally, to further highlight the applicability of such raw materials, the review of the development in several multidisciplinary fields was presented.